Two new Allium (A. sect. Cupanioscordum, Amaryllidaceae) species from Greece - Trigas, Panayiotis; Kalpoutzakis, Eleftherios; Constantinidis, Theophanis (Phytotaxa, 2017)
Allium iatrouinum from Evvia Island (W Aegean, Greece) and A. pycnotrichum from Mt. Parnon (SE Peloponnisos, Greece) are described and illustrated. They belong to A. sect. Cupanioscordum, which includes ca. 24 species so far, mainly distributed in the Mediterranean region. Both species are diploid/dysploid (2n = 2x = 14), related to each other and also related to other dysploid members of the A. cupanii group, especially A. hirtovaginatum (W Turkey) and A. maghrebinum (Tunisia, Algeria). The new species grow in rocky habitats and occur in restricted mountain areas, where they flower in summer, mostly from July to August.